2007
DOI: 10.1186/1477-9560-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Influenza infection and risk of acute pulmonary embolism

Abstract: In this clinical study, influenza infection was not associated with an increased risk of acute pulmonary embolism. The ILI score is non-specific in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Although it is time consuming, CFT was chosen to screen patients' samples for recent influenza. Indeed, CFT preferentially detects IgM and provides a particularly reliable means to detect recent viral infection [24][25][26][27]. This screening approach was then confirmed by strainspecific HIAs for cases related to influenza A virus.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is time consuming, CFT was chosen to screen patients' samples for recent influenza. Indeed, CFT preferentially detects IgM and provides a particularly reliable means to detect recent viral infection [24][25][26][27]. This screening approach was then confirmed by strainspecific HIAs for cases related to influenza A virus.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is another established risk factor for PE [9], and in certain cases, PE has been associated with influenza [10] or cytomegalovirus infection [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Although vascular events were shown to increase in viral influenza infections in one study, another study reported an important connection between seasonal influenza infections and venous thromboembolism [7, 8]. …”
Section: Discussionmentioning
confidence: 99%